2017
DOI: 10.1140/epjc/s10052-017-5137-6
|View full text |Cite
|
Sign up to set email alerts
|

Possible $$D^{(*)}\bar{D}^{(*)}$$ D ( ∗ ) D ¯ ( ∗ ) and $$B^{(*)}\bar{B}^{(*)}$$ B ( ∗ ) B ¯ ( ∗ ) molecular states in the extended constituent quark models

Abstract: The possible neutral D ( * ) D( * ) and B ( * )B( * ) molecular states are studied in the framework of the constituent quark models, which is extended by including the schannel one-gluon exchange. Using different types of quarkquark potentials, we solve the four-body Schrödinger equation by means of the Gaussian expansion method.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 71 publications
0
127
1
2
Order By: Relevance
“…[86][87][88][89][90][91][92] Two-terminal circuit elements, such as resistive switching memristors, [93][94][95][96][97][98][99] have recently been utilized for this purpose in neuromorphic architectures for their simplicity and power efficiency. [12,13,[100][101][102][103][104][105][106] Volatility of resistive switching in Ag-based ECM threshold switches has been reported for realizing neuronal functions like short-term synaptic plasticity (STP), [7,12] short-term plasticity to Adv. Funct.…”
Section: Artificial Synapsesmentioning
confidence: 99%
“…[86][87][88][89][90][91][92] Two-terminal circuit elements, such as resistive switching memristors, [93][94][95][96][97][98][99] have recently been utilized for this purpose in neuromorphic architectures for their simplicity and power efficiency. [12,13,[100][101][102][103][104][105][106] Volatility of resistive switching in Ag-based ECM threshold switches has been reported for realizing neuronal functions like short-term synaptic plasticity (STP), [7,12] short-term plasticity to Adv. Funct.…”
Section: Artificial Synapsesmentioning
confidence: 99%
“…In the current research, GO‐g‐PAA was employed as nanofiller to fabricate nanocomposite hydrogels. GO‐g‐PAA was prepared by ceric salt initiated surface graft polymerization of AA onto GO according to the literature . GO and GO‐g‐PAA were characterized by FTIR, TGA, and TEM.…”
Section: Resultsmentioning
confidence: 99%
“…First, GO‐g‐PAA was prepared by ceric salt initiated surface graft polymerization of AA onto GO according to the method in literature . Typically, desired amount of GO was dispersed into water by sonication in ice‐water bath to get 100 mL of 0.1 wt % aqueous suspension, then 6 g acrylic acid was added and mixed.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that a crossbar structure based on memristors can accelerate various artificial neural networks (ANNs) by directly mapping vector-matrix multiplication (VMM), a most intensive computing component, to electrical parameters relying on Ohm's law and Kirchhoff's law. [6,7] Under this principle, the VMM computing process directly happened in situ, thus avoiding the memory wall (von Neumann Bottleneck) caused by fetching data from memory. Especially in supervised learning, it can reduce the computational complexity of feed forward process and backpropagation from NP to P. [8] Therefore, current studies mostly focus on classification and regression tasks to make use of this new computing mechanism as a complement to complementary metal oxide semiconductor (CMOS) circuits.…”
Section: Introductionmentioning
confidence: 99%